Profiling Humoral Immunity After Mixing and Matching COVID-19 Vaccines Using SARS-CoV-2 Variant Protein Microarrays - Kuo, Ho-Chang; Kuo, Kuang-Che; Du, Pin-Xian; Keskin, Batuhan Birol; Su, Wen-Yu; Ho, Tzong-Shiann; Tsai, Pei-Shan; Pau, Chi Ho; Shih, Hsi-Chang; Huang, Ying-Hsien; Weng, Ken-Pen; Syu, Guan-Da (Molecular & cellular proteomics, 2023)
In November 2022, 68% of the population received at least one dose of COVID-19 vaccines. Owing to the ongoing mutations, especially for the variants of concern (VOCs), it is important to monitor the humoral immune responses after different vaccination strategies. In this study, we developed a SARS-CoV-2 variant protein microarray that contained the spike proteins from the VOCs, e.g., alpha, beta, gamma, delta, and omicron, to quantify the binding antibody and surrogate neutralizing antibody. Plasmas were collected after two doses of matching AZD1222 (AZx2), two doses of matching mRNA-1273 (Mx2), or mixing AZD1222 and mRNA-1273 (AZ+M). The results showed a significant decrease of surrogate neutralizing antibodies against the receptor-binding domain in all VOCs in AZx2 and Mx2 but not AZ+M. A similar but minor reduction pattern of surrogate neutralizing antibodies against the extracellular domain was observed. While Mx2 exhibited a higher surrogate neutralizing level against all VOCs compared with AZx2, AZ+M showed an even higher surrogate neutralizing level in gamma and omicron compared with Mx2. It is worth noting that the binding antibody displayed a low correlation to the surrogate neutralizing antibody (R-square 0.130–0.382). This study delivers insights into humoral immunities, SARS-CoV-2 mutations, and mixing and matching vaccine strategies, which may provide a more effective vaccine strategy especially in preventing omicron. [Display omitted] •Establish CoVariant protein arrays including spike proteins from wild-type to omicron variants.•Concurrently detect neutralizing and binding antibodies against multiple SARS-CoV-2 variants.•Mixing of AZD1222 and mRNA-1273 generates better humoral immunity against omicron than matching. Owing to the ongoing mutations of SARS-CoV-2, we developed an up-to-date CoVariant protein microarray to profile the humoral immunity. We collected plasmas from healthy subjects who underwent two doses of matching (AZD1222 ×2 or mRNA-1273 ×2) and two doses of mixing (AZD1222 + mRNA-1273). We found that mixing generates more surrogate neutralizing activity against gamma and omicron than matching. This study not only provides a high-throughput tool but also delivers a vaccine strategy to fight against SARS-CoV-2 mutations.